An exploration of the relationship between school experience and self-identity for young people with Autism Spectrum Disorder - Rowark, Hannah (2018)
To date, no research has explored the relationship between UK school experience and self-identity for young people with Autism Spectrum Disorder (ASD). Within this study, it is argued that identity is an adaptive process that utilises experience of the sociocultural context to generate a ‘self’. Reviewed literature additionally suggests that school may be an important domain of identity development. Using a Narrative Orientated Inquiry (NOI) methodology, this research examines identity constructs within school experience narratives produced by young people who have a diagnosis of ASD. Participants were five mainstream secondary school (MSS) students (four males and one female) with a diagnosis of ASD (including Asperger Syndrome), sound expressive language skills and no additional diagnoses. Narrative Interviews (Mishler 1986a, 1986b) were conducted. Three interpretive perspectives, in accordance with NOI, were used to analyse transcripts: Separation of ‘fabula’ from ‘sjuzet’ (Hiles and Čermák, 2008); The Holistic-Content interpretive perspective (Lieblich, Tuval-Mashiach and Zilber, 1998); and Critical Narrative Analysis (Emerson and Frosh, 2004). Member checks were carried out. The stories imply that being a young person with ASD at an MSS can be restrictive and disempowering. Findings can be seen to support the proposed theory of identity, suggesting the relationship between school experience and self-identity for young people with a diagnosis of ASD may be an adaptive one, where school experience is the material subject to the process of identity. Findings appear to show that school experience may hinder, through restrictive systems and structures, or help the development of self-identity for young people with ASD. Where young people with ASD can experience free choice and receive support, not least through school staff empathy and understanding, findings suggest they may be aided in developing self-identity. Peer friendships may also potentially afford the opportunity for young people with ASD to learn about themselves, although further research is required in this area.